Methods and Experimental Protocols to Design a Simulated Bio-Mimetic Quadruped Robot. (24th May 2013) - Daou, Hadi El; Libourel, Paul-Antoine; Renous, Sabine; Bels, Vincent; Guinot, Jean-Claude
Abstract This paper presents a bio-mimetic approach to design and simulate a tortoise-like virtual robot. This study takes a multidisciplinary approach: from in vivo and in vitro experiments on animals, data are collected and used to design, control and simulate a bio-mimetic virtual robot using MD ADAMS platform. From the in vitro experiments, the geometrical and inertial properties of body limbs are measured, and a model of tortoise kinematics is derived. From the in vivo experiments the contact forces between each limb and the ground are measured. The contributions of hind and forelimbs in the generation of propelling and braking forces are studied. The motion of the joints between limb segments are recorded and used to solve the inverse kinematics problem. A virtual model of a tortoise-like robot is built; it is a linkage of 15 rigid bodies articulated by 22 degrees of freedom. This model is referred to as TATOR II. It has the inertial and geometrical properties measured during the in vitro experiments. TATOR II motion is achieved using a Proportional-Derivative controller copying the joint angle trajectories calculated from the in vivo experiments.